A shiny fragmentary skeleton: The World Bank and workers' human rights in the 2013 World Development Report - Etchichury, Horacio Javier (2014)
Fil: Etchichury, Horacio Javier. Universidad Nacional de Córdoba. Facultad de Derecho; Argentina.